2011
DOI: 10.1016/j.jacc.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Early Repolarization Pattern in the General Population

Abstract: Objectives To describe the clinical correlates and heritability of the early repolarization pattern (ERP) in two large population-based cohorts. Background There is growing recognition that ERP is associated with adverse outcomes. Methods Participants of the Framingham Heart Study (FHS, n = 3,995) and the Health 2000 Survey (H2K, n = 5,489) were included. ERP was defined as J-point elevation ≥0.1 mV in ≥2 leads in either the inferior (II, III, aVF) or lateral (I, aVL, V4–6) territory or both. We tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(64 citation statements)
references
References 15 publications
3
58
3
Order By: Relevance
“…The association of a initially existing J-wave pattern with future arrhythmic complications during acute STEMI was explained by the presence of heterogeneity of ventricular repolarization as a substrate predisposing to the development of ventricular arrhythmias in the setting of an acute ischemia trigger (22). In our study J-wave point elevation was observed in 0,2%, that is much lower than in the above mentioned studies -11-16% (18,19), and than the reported early repolarization (ER) prevalence in general population -4.5% (23). However, ER is known to be an age-dependant phenomenon, and in age group 60-70 years, corresponding the average age at the moment of historical ECG in our study, its prevalence appears to be in the range of 1.5% in women and 2-3% in man (23) thus being in line with our observations.…”
Section: Discussioncontrasting
confidence: 51%
“…The association of a initially existing J-wave pattern with future arrhythmic complications during acute STEMI was explained by the presence of heterogeneity of ventricular repolarization as a substrate predisposing to the development of ventricular arrhythmias in the setting of an acute ischemia trigger (22). In our study J-wave point elevation was observed in 0,2%, that is much lower than in the above mentioned studies -11-16% (18,19), and than the reported early repolarization (ER) prevalence in general population -4.5% (23). However, ER is known to be an age-dependant phenomenon, and in age group 60-70 years, corresponding the average age at the moment of historical ECG in our study, its prevalence appears to be in the range of 1.5% in women and 2-3% in man (23) thus being in line with our observations.…”
Section: Discussioncontrasting
confidence: 51%
“…A high incidence of an ER pattern in the inferolateral leads has been reported in patients with idiopathic VF 3, 4, 5. Implantable cardioverter defibrillator implantations are recommended in patients with ERS who have survived a cardiac arrest, however, the medical therapy for ERS is still challenging 6, and on the other hand, quinidine is effective for preventing recurrence of ventricular arrhythmias in BrS 7.…”
Section: Discussionmentioning
confidence: 99%
“…In black people this pattern is particularly prevalent, however, these subjects were underrepresented in diverse studies and their arrhythmic risk is still undetermined. In athletes ERP shows a higher prevalence than in the general population: a presence in 20% of noncompetitive and almost 90% in competitive athletes [5,6]. Table I.…”
Section: Diagnostic Criteria Prevalencementioning
confidence: 99%
“…Observing different patient cohorts, ERP produced an increase of 4 to 10 fold in the occurrence of sudden cardiac death, the maximal incidence being reached between 35 and 45 years [5,6].…”
Section: Diagnostic Criteria Prevalencementioning
confidence: 99%